(The presentation that follows is a very light introduction. For more austere results, consult Manuscript 1).
Let's begin with some notation. Let n in N be a positive integer. We define as usual:
n! = 1*2*3*...*(n-1)*n.
Now we will define a new sequence of iterated factorials for n in N, as follows:
hf(n,k) = {n! iff k=1, [hf(n,k-1)]!, iff k > 1}. (1)
hf(n,2) = [n!]!, hf(n,5) = [[[[n!]!]!]!]!, etc. Where no confusion shall arise, we will use hf(n,k) = n!!...!, (k-"!"s). Some examples with Maple:
3!! = 720
4!! = 620448401733239439360000
3!!! =~ .2601218944 * 101747
etc.
We also use the hyperpower function defined here as:
F(x,y,k) = {xy iff k =1, xF(x,k-1), iff k > 1}, so,
F(x,1,1) = x,
F(x,1,2) = 2x = xx,
F(x,y,2) = xxy
...
F(x,1,k) = kx = xxx...x (k-x's).
First, some elementary facts.
The comparison property of divisibility:
a | b and b =/= 0, => |a| ≤ |b|. (1)
Proof:
In any standard Number Theory book.
Corollary:
a | b and a, b > 0, => a≤b.
A couple of immediate facts about the sequence hf(n,k):
Lemma #1:
If m and n are in N, then: m≤n <=> hf(m,k) ≤ hf(n,k), for all positive k.
Proof:
Trivial by induction on k. The factorial sequence is 1-1 and strictly increasing.
Lemma #2:
If m and n are in N, then m≤n <=> m! | n!
Proof:
If m≤n, clearly m! | n!. On the other hand, m! | n!, along with the corollary, => m! ≤n!, and the lemma follows from lemma #1 (for k=1).
Lemma #3:
If m and n are in N, then: m≤n <=> hf(m,k) | hf(n,k), for all k in N.
Proof:
By induction on k. For k=1, this is lemma #2. Assume that the lemma holds for k in N, k>1. That is, m≤n <=> hf(m, k) | hf(n,k). From the induction hypothesis, m≤n, => hf(m,k) | hf(n,k). From the corollary, => hf(m,k) ≤ hf(n,k). From lemma #2, => [hf(m,k)]! | [hf(n,k)]!, => hf(m,k+1) | hf(n, k+1).
For the reverse, assume hf(m,k+1) | hf(n, k+1). From the corollary, => hf(m,k+1) ≤ hf(n,k+1). From lemma #1 (for arbitrary k), => m≤n, and the lemma follows.
Let's now look how fast these hyperfactorials grow. We will need the following two lemmas along with their corollaries.
Lemma #4:
If k ≥ 1 then for all n in N, hf(n+1,k+1) - hf(n,k+1) > hf(n,k+1)*[nhf(n+1,k) - hf(n,k) - 1]
Proof:
Directly or by induction. The direct proof is shorter. By lemma #3, hf(n,k+1) | hf(n+1,k+1), => hf(n+1,k+1) - hf(n,k+1) = 1*2*...*hf(n+1,k) - 1*2*...*hf(n,k) = 1*2*...*hf(n,k)*[(hf(n,k)+1)*(hf(n,k)+2)*...(hf(n+1,k)) - 1] = hf(n,k+1)*[(hf(n,k)+1)*(hf(n,k)+2)*...(hf(n+1,k)) - 1]. If k ≥1, => hf(n,k) + j > n, for all j. There are hf(n+1,k) - hf(n,k) terms in the product, and the lemma follows.
Corollary:
If k ≥1 then for all n in N, hf(n+1,k) - hf(n,k) > kn = F(n,1,k)
Sketch of Proof:
Iterate the weaker inequality of lemma #4. hf(n+1,k+1) - hf(n,k+1) > nhf(n+1,k) - hf(n,k), and use induction.
Lemma #5:
If k ≥1, then hf(n,k)/hf(n+1,k) < 1/kn = 1/F(n,1,k)
Proof:
Using lemma #3, hf(n,k) | hf(n+1,k), => hf(n,k)/hf(n+1,k) =
Using the corollary above, the product contains at most k-1n terms, and hf(n,k-1) + j > n, for all j, => hf(n,k)/hf(n+1,k) < 1/n k-1n = 1/kn and the lemma follows.
Lemma #6:
If k ≥1, then
converges for all x.
Proof:
If k=1, we get the exp series. If k>1 then |a(n+1)/a(n)| = |x*hf(n,k)/hf(n+1,k)|. By lemma #5, the above tends to 0, for all x.
Lemma #7:
If k =1 then the series,
converges for |x| < 1/e. If k > 1 then it converges for all x.
Proof:
If k=1, the Ratio test gives limn->+∞|a(n+1)/a(n)| = |ex| < 1, provided |x| < 1/e. >If k > 1, the same test gives |a(n+1)/a(n)| = (n+1)(n+1)*x/[nn*(n+1)] *(n+1)*hf(n,k)/hf(n+1,k)|. Using lemma #5, |a(n+1)/a(n)| < |(n+1)(n+1)*x/[nn*(n+1)] *(n+1)/kn|
limn->+∞[(n+1)(n+1)*x/[nn*(n+1)]] = ex, as before, and obviously limn->+∞(n+1)/kn = 0, for k > 1, and the rest of the lemma follows.
Can we up the stakes a bit? What about xxn on the numerator of the series instead of xn? Let's see.
Lemma #8:
If k > 2 then the series:
converges for all x.
Proof:
Using lemma #5 |a(n+1)/a(n)| < |xxn*[x-1]/kn|. For sufficiently large n, x < n, => |a(n+1)/a(n)| < |nnn/kn|=|3n/kn|, so if k > 2, => limn->+∞|a(n+1)/a(n)| < 1, and the lemma follows.
Lemma #9:
If k > m - 1 then the series,
converges for all x.
Proof:
Similar to the proof of lemma #8.
Let's see if we can go further up. What about nx on the numerator?
Lemma #10:
If k ≥1 then the series,
converges for x in (0,e(1/e)].
Proof:
Using lemma #5, |a(n+1)/a(n)| < |n+1x/nx * 1/kn|. When x is in [(1/e)e,e(1/e)], limn->+∞nx = e-W(-ln(x)), by the article on Infinite Exponentials, so, limn->+∞n+1x/nx = 1, while limn->+∞1/kn = 0, for k ≥1, and the lemma follows.
If on the other hand, x is in (0,(1/e)e), |a(n+1)/a(n)| = |n+1x/nx*hf(n,k)/hf(n+1,k)|, and nx is a two cycle, bounded above by 1 and below by 0. This means that we may have problems with the odd subsequence: 2m+1x, on the denominator. Using lemma #5, => |a(n+1)/a(n)| < |n+1x/nx*1/kn|, as before, and limm->+∞2mx = a < 1, with a being a solution to xxa=a, (See Solving the Second Real Auxiliary Exponential Equation), limm->+∞2m+1x = b > 0, b < a, and with b given by xa = b, above. This means that |n+1x/nx|, n in N, is a two-cycle. We check the even and odd subsequences: limm->+∞|a(2m+1)/a(2m)| ≤ limm->+∞|2m+1x/2mx*1/k(2m)| = |b/a*0| = 0, while, limm->+∞|a(2m+2)/a(2m+1)| ≤ limm->+∞|2m+2x/2m+1x*1/k(2m+1)| = |a/b*0| = 0, and the lemma follows[1].
Lemma #11
If k >1 then for all n in N, hf(n+1,k+1) - hf(n,k) > hf(n,k)*[nhf(n+1,k) - hf(n,k-1) - 1]
Proof:
Directly or by induction. The direct proof is shorter. By lemma #3, hf(n,k) | hf(n+1,k), and obviously hf(n+1,k) | hf(n+1,k+1), => hf(n+1,k+1) - hf(n,k+1) = 1*2*...*hf(n+1,k) - 1*2*...*hf(n,k-1) = 1*2*...*hf(n,k-1)*[(hf(n,k-1)+1)*(hf(n,k-1)+2)*...(hf(n+1,k)) - 1] = hf(n,k)*[(hf(n,k-1)+1)*(hf(n,k-1)+2)*...(hf(n+1,k)) - 1]. If k >1, => hf(n,k-1) + j > n, for all j. There are hf(n+1,k) - hf(n,k-1) terms in the product, and the lemma follows.
Corollary:
If k >1 then for all n in N hf(n+1,k+1) - hf(n,k) > k+1n = F(n,1,k+1)
Proof
Iterate the weaker inequality of lemma #11, hf(n+1,k+1) - hf(n,k) > nhf(n+1,k) - hf(n,k-1), and use induction.
Lemma #12:
If k >1, then, hf(n,k)/hf(n+1,k+1) < 1/k+1n = 1/F(n,1,k+1)
Proof:
By lemma #3, hf(n,k) | hf(n+1,k), and obviously hf(n+1,k) | hf(n+1,k+1), => hf(n,k)/hf(n+1,k+1) =
Using the corollary above, the product contains at most kn terms, and hf(n,k-1) + j > n, for all j, => hf(n,k)/hf(n+1,k)< 1/n kn = 1/k+1n and the lemma follows.
We can still go further.
Lemma #13:
The series,
converges for all x > 0.
Proof:
Using lemma #12, |a(n+1)/a(n)| < |n+1x/nx*1/n+1n|. If x is in [(1/e)e,e(1/e)] then limn->+∞nx = e-W(-ln(x)), so, => limn->+∞|n+1x/nx| = 1, as before and limn->+∞|1/n+1n| = 0, and the result follows. If x > e(1/e), for sufficiently large n, x < n, => n+1x < n+1n. Using lemma #12, => |a(n+1)/a(n)| < |1/nx|, consequently, limn->+∞|a(n+1)/a(n)| = 0, and the result follows.
If on the other hand, x is in (0,(1/e)e), |a(n+1)/a(n)| = |n+1x/nx*hf(n,n)/hf(n+1,n+1)|, and nx is again a two cycle, bounded above by 1 and below by 0. Using lemma #12, |a(n+1)/a(n)| < |n+1x/nx*1/n+1n|, as before, and limm->+∞2mx = a < 1, with a being a solution to xxa=a, (See Solving the Second Real Auxiliary Exponential Equation), limm->+∞2m+1x = b > 0, b < a, and with b given by xa = b, above. This means that, |n+1x/nx|, n in N, is a two-cycle. We check the even and odd subsequences: limm->+∞|a(2m+1)/a(2m)| ≤ limm->+∞|2m+1x/2mx*1/2m+1(2m)| = |b/a*0| = 0, while, limm->+∞|a(2m+2)/a(2m+1)| ≤ limm->+∞|2m+2x/2m+1x*1/2m+2(2m+1)| = |a/b*0| = 0, and the lemma follows.